Effects of coach leadership and coach-athlete relationship on collective efficacy - Hampson, R.; Jowett, S. (Scandinavian Journal of Medicine & Science in Sports, 2014)
The study examined the independent and combined effects of coach leadership and coaching relationships on team efficacy. A total of 150 sport performers from football teams across a range of competitive levels completed a multisection self-report instrument to assess their individual perceptions of the level of collective efficacy, the type of coach leadership, and the quality of the coach-athlete relationship. Multiple regression analyses revealed that perceptions of both coach leadership and the coach-athlete relationship predicted variance in team efficacy. Overall, the findings suggest that the quality of coach-athlete relationships added to the prediction of individuals` collective efficacy beyond what was predicted by coaches` behaviors of leadership alone. Limitations and future research directions are discussed.